2013
DOI: 10.1161/circep.113.000749
|View full text |Cite
|
Sign up to set email alerts
|

Unipolar Signal Modification as a Guide for Lesion Creation During Radiofrequency Application in the Left Atrium

Abstract: P ulmonary vein isolation (PVI) is the cornerstone for catheter ablation procedures in patients with paroxysmal atrial fibrillation (AF).1 However, there is current concern about the durability of PVI because the PV reconnection rate has been recognized as substantial and clearly associated with the recurrence of paroxysmal AF episodes. 2 Editorial see p 1050 Clinical Perspective on p 1102PV reconnection may be related to the inability to create transmural and irreversible lesions around PV ostia. 3,4 In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 8 publications
0
47
0
Order By: Relevance
“…Controversial data about influence of older age on the periprocedural complications were published. For example, one study showed no significant difference between major complication rates of the AF ablation in three different age groups of patients, namely <65 years, [65][66][67][68][69][70][71][72][73][74] years and ≥75 years (1.6% vs. 1.7% vs. 2.9%, p=ns) [126]. On the contrary, the other two studies demonstrated strong association between the occurrence of complication and older age of >70 and ≥75 years [127,128].…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…Controversial data about influence of older age on the periprocedural complications were published. For example, one study showed no significant difference between major complication rates of the AF ablation in three different age groups of patients, namely <65 years, [65][66][67][68][69][70][71][72][73][74] years and ≥75 years (1.6% vs. 1.7% vs. 2.9%, p=ns) [126]. On the contrary, the other two studies demonstrated strong association between the occurrence of complication and older age of >70 and ≥75 years [127,128].…”
Section: Agementioning
confidence: 99%
“…Subsequent ablation of these fibers can significantly increase the efficiency of the first intervention [62][63][64]. It seems that the loss of capture on the ablative line, ablation guided by atrial unipolar signal modification and development of contact-force technology could provide better transmurality, continuity and durability of ablative lesion [27,[65][66][67][68].…”
Section: Figure 2 Catheter Ablation Of Paroxysmal Af: Elimination Ofmentioning
confidence: 99%
“…6 Similarly, the creation of a completely positive unipolar signal has also been associated with transmural lesion formation, and achievement of this endpoint has been associated with improved outcomes after AF ablation. 7 However, the assessment of real-time EGM diminution is difficult to quantify in real time, and can also be misleading, as changes in catheter position and cathetertissue contact can alter EGM morphology and amplitude. Indeed EGM diminution can reflect either actual tissue destruction or, simply, the absence of adequate contact between the ablation catheter and the tissue.…”
Section: Rf Lesion Assessmentmentioning
confidence: 99%
“…The ultimate solution is improved front-end filtering so that acquired and displayed waveforms are visible and clean during the application of RF energy. 17,18,[21][22][23] Unfortunately, in conventional recording systems, unipolar signals referenced to WCT tend to be noisy. The low cut-off frequency for the highpass filter requires an expanded dynamic range to fully capture the recorded signals with baseline drift.…”
Section: Pitfalls Of Current Recording and Mapping Systems And Possibmentioning
confidence: 99%